Shocks, livestock asset dynamics and social capital in Ethiopia - Mogues, Tewodaj (International Food Policy Research Institute, 2006)
This paper uses household survey panel data of 416 rural households to study livestock asset dynamics in the north-east of Ethiopia. The period under examination (1996-2003) was marked by severe environmental shocks, including a series of droughts. Using as point of departure the literature on the evolution of productive assets in the presence of risk, which relates asset paths to initial endowments, we test the hypothesis of wealth divergence and the existence of asset poverty traps. Results indicate rather that livestock asset dynamics are marked by convergence over time. Examining the role of social capital in recovery and growth of households’ endowments, both local social relationships as well as ‘bridging’ social capital seem to have a positive effect on asset holdings directly, as well as indirectly by mitigating the impact of income shocks on livestock capital.